2008
DOI: 10.1152/ajpregu.00688.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyunsaturated fatty acids on hibernation and torpor: a review and hypothesis

Abstract: Polyunsaturated fatty acids (PUFAs) can have strong effects on hibernation and daily torpor in mammals. High dietary PUFA contents were found to increase proneness for torpor, decrease body temperatures, prolong torpor bout duration, and attenuate hibernation mass loss. The mechanism by which PUFAs enhance torpor and hibernation is unknown, however. On the basis of a review of the literature, and on reexamining our own data on alpine marmots, we propose that effects on hibernation are not due to PUFAs in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(151 citation statements)
references
References 79 publications
10
139
1
1
Order By: Relevance
“…Indeed, alpine meadows at higher altitude are physiologically younger and consequently enriched of α-linolenic acid (Hawke, J.C. 1973) which has been demonstrated affecting hibernation and torpor in mammals (Ruf & Arnold 2008). In accordance our results show that groups inhabiting alpine meadows at lower altitude share larger part of their territory with neighbours underlining the need of incorporating data on vegetation quality to increase our knowledge on inter group competition in this species.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, alpine meadows at higher altitude are physiologically younger and consequently enriched of α-linolenic acid (Hawke, J.C. 1973) which has been demonstrated affecting hibernation and torpor in mammals (Ruf & Arnold 2008). In accordance our results show that groups inhabiting alpine meadows at lower altitude share larger part of their territory with neighbours underlining the need of incorporating data on vegetation quality to increase our knowledge on inter group competition in this species.…”
Section: Discussionsupporting
confidence: 83%
“…To interpret exercise performance effects we would need to understand sex differences in the energetic cost or energetic strategies associated with migratory flight. However, sexbased variation in the muscle PL n-6:n-3 ratio is consistent with the Ruf and Arnold (Ruf and Arnold, 2008) hypothesis that an increased n-6:n-3 ratio is associated with torpor use. During spring migration, male hoary bats readily use torpor while females rarely lower their body temperature (Cryan and Wolf, 2003), and accordingly we observed an increased n-6:n-3 ratio in males and a decreased ratio in females.…”
Section: Fa Profilessupporting
confidence: 85%
“…Based on the Munro and Thomas (Munro and Thomas, 2004) framework, migrating insectivorous bats should seek to maximize PUFAs. However, another review suggested that a high n-6:n-3 ratio is important for maintaining membrane function at low body temperatures (Ruf and Arnold, 2008). Male hoary bats are more likely to use torpor during spring migration than females (Cryan and Wolf, 2003), and therefore we predicted that sexes would differ in muscle PL composition during migration.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…If this is true for n-3 and n-6 PUFA, then selection for diets high in PUFA could be important for successful migration. Similar arguments have been made for diet shifts in mammals preparing to hibernate (Ruf and Arnold, 2008). The evidence regarding the effects of unsaturation in general, and PUFA in particular, on migratory birds has been reviewed previously (Guglielmo, 2010;Pierce and McWilliams, 2014;Price, 2010;Weber, 2009), so I will only cover this briefly here and discuss new findings.…”
Section: Potential Benefits Of Unsaturated Fatty Acids For Migrantsmentioning
confidence: 73%